Beta cell dedifferentiation in type 1 diabetes: sacrificing function for survival? - Webster, Kierstin L.; Mirmira, Raghavendra G. (Frontiers in Endocrinology, 2024)
The pathogeneses of type 1 and type 2 diabetes involve the progressive loss of functional beta cell mass, primarily attributed to cellular demise and/or dedifferentiation. While the scientific community has devoted significant attention to unraveling beta cell dedifferentiation in type 2 diabetes, its significance in type 1 diabetes remains relatively unexplored. This perspective article critically analyzes the existing evidence for beta cell dedifferentiation in type 1 diabetes, emphasizing its potential to reduce beta cell autoimmunity. Drawing from recent advancements in both human studies and animal models, we present beta cell identity as a promising target for managing type 1 diabetes. We posit that a better understanding of the mechanisms of beta cell dedifferentiation in type 1 diabetes is key to pioneering interventions that balance beta cell function and immunogenicity.